9-3m=-m-(4m+1)

Simple and best practice solution for 9-3m=-m-(4m+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9-3m=-m-(4m+1) equation:



9-3m=-m-(4m+1)
We move all terms to the left:
9-3m-(-m-(4m+1))=0
We calculate terms in parentheses: -(-m-(4m+1)), so:
-m-(4m+1)
We add all the numbers together, and all the variables
-1m-(4m+1)
We get rid of parentheses
-1m-4m-1
We add all the numbers together, and all the variables
-5m-1
Back to the equation:
-(-5m-1)
We get rid of parentheses
-3m+5m+1+9=0
We add all the numbers together, and all the variables
2m+10=0
We move all terms containing m to the left, all other terms to the right
2m=-10
m=-10/2
m=-5

You can always share this solution

See similar equations:

| N-5=3n+5 | | 70x+80x=225 | | 5-(4x+8)=5-4x-8 | | 3x+5+2x=5(2+x) | | 121/x=55/5 | | -1.7(2x-5.2=34 | | 8y-10-4y+7=0 | | x^2-27x+139=0 | | 4/6x=2,800 | | 76x+76=?76x+76 | | ?76x+76=76x+76 | | 1-2k=1-2k | | r+2=11-2r | | -2x-6-4x=2-2x-5x | | 1/3=c/6 | | 27-(2c+3=2(c+7)+c | | -5r-2=r+2-5r | | 6x+9x+9=90 | | -3x-7x-13=-7x+2 | | 2+x+4x=3x-8 | | 10x+17=14x+29 | | -x=8x-3x | | ?76x+76=?76x+76 | | 12-6m=7-5m | | 12+m=-5m+4m | | 9x-4=8x+5x | | -4(11n+15)=19n-20n+10 | | 12+m=7-5m | | -4a-4=-2a+6 | | -5n+7=4-8n | | -2(8k-9)=18+16k | | p+6-5=9+2p |

Equations solver categories